2015
DOI: 10.1051/0004-6361/201526410
|View full text |Cite
|
Sign up to set email alerts
|

Probing highly obscured, self-absorbed galaxy nuclei with vibrationally excited HCN

Abstract: We present high resolution (0. ′′ 4) IRAM PdBI and ALMA mm and submm observations of the (ultra) luminous infrared galaxies ((U)LIRGs) IRAS17208-0014, Arp220, IC860 and Zw049.057 that reveal intense line emission from vibrationally excited (ν 2 =1) J=3-2 and 4-3 HCN. The emission is emerging from buried, compact (r <17-70 pc) nuclei that have very high implied mid-infrared surface brightness >5 × 10 13 L ⊙ kpc −2 . These nuclei are likely powered by accreting supermassive black holes (SMBHs) and/or hot (>200 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
184
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(204 citation statements)
references
References 73 publications
17
184
2
1
Order By: Relevance
“…In this case, we observed a significant offset of 0.045 of the spectral feature toward the northwest (PA ∼ 120 • ) with respect to the continuum, in good agreement with the plane of rotation measured with HCN (PA ∼ 45 • Scoville et al 2015), but not with the gradient observed with CO in the inner region (Sakamoto et al 1999;Rangwala et al 2015). Again, when peering through the opaque mid-IR dust, the HCN v 2 = 1 f line might be probing the kinematics of a hot dusty circumnuclear disk, as has been proposed by Aalto et al (2015b), with a radius of ∼18 pc.…”
Section: Vibrational Emission Within the Opaque Dustsupporting
confidence: 84%
See 4 more Smart Citations
“…In this case, we observed a significant offset of 0.045 of the spectral feature toward the northwest (PA ∼ 120 • ) with respect to the continuum, in good agreement with the plane of rotation measured with HCN (PA ∼ 45 • Scoville et al 2015), but not with the gradient observed with CO in the inner region (Sakamoto et al 1999;Rangwala et al 2015). Again, when peering through the opaque mid-IR dust, the HCN v 2 = 1 f line might be probing the kinematics of a hot dusty circumnuclear disk, as has been proposed by Aalto et al (2015b), with a radius of ∼18 pc.…”
Section: Vibrational Emission Within the Opaque Dustsupporting
confidence: 84%
“…Vibrational HCN levels are efficiently excited by 14 µm continuum photons provided that T B > 100 K (Aalto et al 2015b). Our data show that the peak of the continuum emission matches the position at which vibrationally excited emission is found, which supports the idea that the emission is excited through continuum photons.…”
Section: Hcn Excitation Of Vibrational Levelssupporting
confidence: 79%
See 3 more Smart Citations